Mathematical Aptitude Analysis of Prospective Teachers at the Indian Institute of Teacher Education - Dharmik Chauhan; Supriya Ranjan (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
In this study, the researcher wants to find the mathematical aptitude of future teachers. The sample taken for the study is the teacher trainees of different colleges under the Indian Institute of Teacher Education, and the technique used is a random sampling technique. An investigation that covers the entire population is challenging to carry out. The population's representative subjects must, therefore, be chosen. An examined and observed sample is a subset of a larger population. DIET Gandhinagar, DIET Ahmedabad, Centre for Education, M. N. Shukla College, A.G. teacher's college. The sample is drawn from the 168 prospective teachers (teacher trainees) enrolled; 84 are from the District Institute of Education and Training, and the remaining 84 are from other colleges. The data is collected through a questionnaire as the research tool. Collected data were analyzed by t-test. The findings denoted that there are some differences between mathematical aptitude concerning gender and based on colleges.